Evaluation of Learning Outcomes Among Practical Nursing Students After Using Three-Dimensional Technology in Their Studies - Alhonkoski, Mika; Veermans, Marjaana; Nurmi, Hanna; Kotonen, Sari; Strandell-Laine, Camilla; Artukka, Kalle; Salminen, Leena (Lippincott, 2025)
There is a lack of evidence-based information on the use of technology in first-aid education. For this reason, this study aimed to describe the learning outcomes of three-dimensional technology among practical nursing students in first-aid courses. In this quasi-experimental study, first-year practical nursing students (n = 59) were divided into intervention group (n = 32) and control group (n = 27). For the intervention group, the first-aid course (a total of 16 hours per group) included three-dimensional images, three-dimensional environments, and three-dimensional printing. For the control group, the teaching was implemented using traditional methods. The data of knowledge (pre, post, and follow-up) and skills (post) were collected. The intervention group obtained statistically significantly higher scores in knowledge in follow-up test than the control group (P = .048). They also performed better on the entire resuscitation protocol (P = .0193) and in the following parts of resuscitation: student call for help, student opens the airway correctly, student checks the breathing correctly, and student has a correct depth in the chest compressions. As a conclusion, three-dimensional technology can enhance students' first-aid knowledge and improve cardiopulmonary resuscitation skills in practical nursing education.